Association of the PNPLA2, SCD1 and Leptin Expression with Fat Distribution in Liver and Adipose Tissue From Obese Subjects - Cruz-Color, Lucía De la; Hernández-Nazará, Zamira Helena; Maldonado-González, Montserrat; Navarro-Muñíz, Eliseo; Domínguez-Rosales, José Alfredo; Torres-Baranda, José Rodrigo; Ruelas-Cinco, Elizabeth del Carmen; Ramírez-Meza, Sandra Margarita; Ruíz-Madrigal, Bertha (Experimental and Clinical Endocrinology & Diabetes, 2019)
The expansion of adipose tissue is regulated by insulin and leptin through sterol regulatory element-binding protein-1c (SREBP-1c), up-regulating lipogenesis in tissues by Stearoylcoenzyme A desaturase 1 (SCD1) enzyme, while adipose triglyceride lipase (ATGL) enzyme is key in lipolysis. The research objective was to evaluate the expression of Sterol Regulatory Element Binding Transcription Factor 1 (SREBF1), SCD1, Patatin Like Phospholipase Domain Containing 2 (PNPLA2), and leptin (LEP) genes in hepatic-adipose tissue, and related them with the increment and distribution of fat depots of individuals without insulin resistance. Thirty-eight subjects undergoing elective cholecystectomy with liver and adipose tissue biopsies (subcutaneous-omental) are included. Tissue gene expression was assessed by qPCR and biochemical parameters determined. Individuals are classified according to the body mass index, classified as lean (control group, n=12), overweight (n=11) and obesity (n=15). Abdominal adiposity was determined by anthropometric and histopathological study of the liver. Increased SCD1 expression in omental adipose tissue (p=0.005) and PNPLA2 in liver (p=0.01) were found in the obesity group. PNPLA2 decreased expression in subcutaneous adipose tissue was significant in individuals with abdominal adiposity (p=0.017). Anthropometric parameters positively correlated with liver PNPLA2 and the expression of liver PNPLA2 with serum leptin. SCD1 increased levels may represent lipid storage activity in omental adipose tissue. Liver PNPLA2 increased expression could function as a primary compensatory event of visceral fat deposits associated to the leptin hormone related to the increase of adipose tissue.
Keywords: fat deposit; obesity; leptin; SCD1; PNPLA2